Molecular Iodine Mediated Regioselective Synthesis of Pyranocoumarins and Bis-Fused Benzo-2H-pyran Derivatives - Majumdar, K. C.; Sinha, Biswajit; Ansary, Inul; Ganai, Sintu; Ghosh, Debankan; Roy, B.; Sridhar, B. (Synthesis, 2014)
A simple and straightforward approach for the regioselective synthesis of pyranocoumarin and bis-fused benzo-2H-pyran derivatives using mild, easy to handle, and cheaper molecular iodine mediated heterocyclization is described.
Keywords: molecular iodine; 6-endo-dig; electrophilic cylization; bis-fused benzo-2H-pyrans; pyranocoumarins